Carbohydrate inhibitors of cholera toxin - Kumar, Vajinder; Turnbull, W. Bruce (Beilstein Journal of Organic Chemistry, 2018)
Cholera is a diarrheal disease caused by a protein toxin released by Vibrio cholera in the host’s intestine. The toxin enters intestinal epithelial cells after binding to specific carbohydrates on the cell surface. Over recent years, considerable effort has been invested in developing inhibitors of toxin adhesion that mimic the carbohydrate ligand, with particular emphasis on exploiting the multivalency of the toxin to enhance activity. In this review we introduce the structural features of the toxin that have guided the design of diverse inhibitors and summarise recent developments in the field.
Keywords: carbohydrate; cholera; multivalency; toxin